Legal Perspectives on Digital Privacy Rights in Civil Law : A Comparative Analysis - Anugerah Rahmat Hidayat; Arif Nur Sahid; Aditia Yuski Fahlevi (International Forum of Researchers and Lecturers, 2024)
This article examines the evolving landscape of digital privacy rights within civil law frameworks. With technological advancements outpacing regulatory measures, there is a growing need for robust legal standards to protect personal information. This study compares privacy regulations across several jurisdictions, assessing the efficacy of existing laws and identifying key challenges faced by policymakers. The article proposes a set of guidelines that could help harmonize digital privacy standards globally, ensuring individual rights are adequately protected in an increasingly interconnected world.